Mechanical properties of polygon oil palm lumber / Ahmad Fauzi Awang@Othman … [et al.] - Awang@Othman, Ahmad Fauzi; Zakaria, Shaikh Abdul Karim Yamani; Ahmad Zaki, Junaiza; Shafie, Amran; Abdul Latif, Nur Hannani; Radzi, Azizol (2012)
The oil palm (Elaeis guineensis) was first introduced to Malaysia in 1917 in Tennamaran Estate, Selangor as a commercial planting. It takes 3 years to mature before it bears fruit. The economic life of the oil palm extends to about 25 years, and after which, they have to be replanted. Huge quantities of biomass waste are generated from the oil palm industry in terms of trunks, fronds, empty fruit bunch and palm kernel. The wastes from these replanting activities are generally left to rot or burn in the field. These studies were observed by using Oil Palm Lumber (OPL) from different height levels (top. middle. bottom) and layers (Ll. L2. L3). These OPL were cut using polygon method. Bending (MOE, MOR) and compression testing were applied to evaluate their mechanical properties. These mechanical properties of OPL can serve as an indicator for predicting the wood behavior for specific end usage. The findings revealed that there was no significant variation between the high levels for both testings. However, there is significant variation between layers for bending testing and no significance for compression testing.